Model Intrapreneurship Leadership pada Kepuasan Stakeholder - Hartoyo, Hartoyo; Fitriaty, Fitriaty; Dahmiri, Dahmiri (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This study aims to find out how the implementation of the strategic development security section activities at the Jambi High Prosecutor's Office in the context of securing the work of national strategic projects and regionally strategic projects in Jambi Province and to determine the effect of intrapreneurship, leadership to satisfaction stakeholder (applicants, service providers, supervisory consultants, etc.) as well as phenomena that occur in these activities such as work not according to the schedule, work not by following with the specifications contained in the contract, lack of quality of work due to pursuing progress, etc. This research was conducted for 2021, using quantitative research methods based on data cross-sectional and collected through a survey questionnaire. The data analysis technique in this study uses Partial Least Square (PLS) with a population of 74 respondents consisting of activity applicants (heads, commitment makers, technical implementation officers), service providers/partners (directors, managers, and field implementers), and consultants supervisors (director, team leader, and field supervisor). The result of this study is intrapreneurship's significant and positive effect on satisfaction stakeholders, Besides that leadership also has a positive and significant impact on satisfaction stakeholders. This study provides insight into how intrapreneurship and leadership in terms of raising personnel and materials as well as coordinating with related parties in securing strategic project development activities, intrapreneurship and leadership have a positive impact on the project being carried out so that it can be carried out time, on target, on budget, and quality to provide satisfaction stakeholder and increase public trust in the effort to maximize the prevention of corruption.